Pengaruh tingkat kemiskinan terhadap angka putus sekolah pada jenjang SD, SMP, dan SMA di Kota Banjarbaru - Nadila, Ayu; Suratno, Suratno; Ratumbuysang, Monry Fraick Nicky Gillian; Permatasari, Melly Agustina (Jurnal Pendidikan Ekonomi (JUPE), 2025)
This study aims to analyze the influence of poverty levels on dropout rates at elementary, junior high, and senior high schools in Banjarbaru City. The method used is quantitative research with comparative descriptive analysis and policy analysis, and data processing using Microsoft Excel software. Time series data from the 2015/2016 to 2024/2025 academic years were obtained from secondary sources such as official reports from the Central Statistics Agency, the Social Services Agency, and related educational institutions. Data collection was conducted through literature studies, so no sampling techniques or questionnaires were required. The results of the study indicate a significant influence between poverty levels and dropout rates. Cempaka District, with 3,471 poor people, recorded the highest dropout rate. Landasan Ulin District, with 2,388 poor people, had a moderate dropout rate. Conversely, North Banjarbaru District, with 1,087 poor people, showed a very low dropout rate. These findings confirm that the higher the poverty level, the greater the risk of children dropping out of school, especially at the senior high school level.